TOXIC MASCULINITY PORTRAYED BY HOMELANDER’S CHARACTER IN THE BOYS GRAPHIC NOVEL - Rizky, Akbar; Saraswati, Rina; Nur Dian Rosyidah, Usma (BASIS (Bahasa dan Sastra Inggris), 2025)
This study explores the concept of toxic masculinity as portrayed in The Boys graphic novel, focusing on the character Homelander. Toxic masculinity refers to harmful behaviors and attitudes—such as dominance, violence, and misogyny—that stem from traditional expectations of masculinity. Using theoretical frameworks by Kupers and Connell, the research employs a qualitative descriptive approach, analyzing all seventy-two issues of The Boys. Data were collected through close reading of the graphic novel, review of existing literature, and examination of dialogue that reflects toxic masculinity. The study addresses two research questions: (1) How is toxic masculinity represented through Homelander’s character? and (2) How does toxic masculinity manifest in gender relations within the story? The findings reveal that Homelander embodies three key aspects of toxic masculinity: misogyny, violence, and dominance. These traits are supported by twenty-two textual examples from the graphic novel. Regarding gender relations, the study identifies three patterns shaped by toxic masculinity: power relations, production relations (control over roles and resources), and cathexis (emotional or sexual attachments influenced by dominance). These are illustrated by seven examples from the text. In conclusion, The Boys uses Homelander to vividly depict toxic masculinity and its harmful impact on gender dynamics. The graphic novel thus serves as a critical commentary on destructive masculine norms in contemporary society.